Pituitary miRNAs target GHRHR splice variants to regulate GH synthesis by mediating different intracellular signalling pathways. Issue 12 (1st December 2020) - Cheng, Yunyun; Chen, Ting; Song, Jie; Teng, Zhaohui; Wang, Chunli; Wang, Siyao; Lu, Guanhong; Feng, Tianqi; Qi, Qien; Xi, Qianyun; Liu, Songcai; Hao, Linlin; et al.
ABSTRACT: Growth hormone (GH), whose synthesis and release are mainly regulated by intracellular signals mediated by growth hormone-releasing hormone receptor (GHRHR), is one of the major pituitary hormones and critical regulators of organism growth, metabolism, and immunoregulation. Pig GHRHR splice variants (SVs) may activate different signalling pathways via the variable C-terminal by alternative splicing, and SVs have the potential to change microRNA (miRNA) binding sites. In this study, we first confirmed the existence of pig GHRHR SVs (i.e., GHRHR, GHRHR SV1 and SV2) and demonstrated the inhibitory effects of critical pituitary miRNAs (i.e., let-7e and miR-328-5p) on GH synthesis and cell proliferation of primary pituitary cells. The SVs of GHRHR targeted by let-7e and miR-328-5p were predicted via bioinformatics analysis and verified by performing dual-luciferase reporter assays and detecting the expression of target transcripts. The differential responses of let-7e, and miR-328-5p to GH-releasing hormone and the changes in signalling pathways mediated by GHRHR suggested that let-7e and miR-328-5p were involved in GH synthesis mediated by GHRHR SVs, indicating that the two miRNAs played different roles by different ways. Finally, results showed that the protein coded by the GHRHR transcript regulated GH through the NO/NOS signalling pathway, whereas that coded by SV1 and SV2 regulated GH through the PKA/CREB signalling pathway, which was confirmed by the changes in signalling pathways after transfecting the expression vectors of GHRHR SVs to GH3 cells. To the best of our knowledge, this paper is the first to report pituitary miRNAs regulate GH synthesis by targeting the different SVs of GHRHR .